Immunization with cDNA Expressed by Amastigotes of Trypanosoma cruzi Elicits Protective Immune Response against Experimental Infection - Boscardin, Silvia B. (American Society for Microbiology, 2003)
Immunization of mice with plasmids containing Trypanosoma cruzi genes induced specific antibodies, CD4(+) Th1 and CD8(+) Tc1 cells, and protective immunity against infection. In most cases, plasmids used for DNA vaccination contained genes encoding antigens expressed by trypomastigotes, the nonreplicative forms of the parasite. In this study, we explored the possibility of using genes expressed by amastigotes, the form of the parasite which replicates inside host cells, for experimental DNA vaccination. For that purpose, we selected a gene related to the amastigote surface protein 2 (ASP-2), an antigen recognized by antibodies and T cells from infected mice and humans, for our study. Using primers specific for the asp-2 gene, four distinct groups of genes were amplified from cDNA from amastigotes of the Y strain of T. cruzi. At the nucleotide level, they shared 82.3 to 89.9% identity with the previously described asp-2 gene. A gene named clone 9 presented the highest degree of identity with the asp-2 gene and was selected for immunological studies. Polyclonal antisera raised against the C terminus of the recombinant protein expressed by the clone 9 gene reacted with an antigen of approximately 83 kDa expressed in amastigotes of T. cruzi. Immunization of BALB/c mice with eukaryotic expression plasmids containing the clone 9 gene elicited specific antibodies and CD4(+) T-cell-dependent gamma interferon secretion. Upon challenge with trypomastigotes, mice immunized with plasmids harboring the clone 9 gene displayed reduced parasitemia and survived lethal infection. We concluded that amastigote cDNA is an interesting source of antigens that can be used for immunological studies, as well as for vaccine development.